2014
DOI: 10.14260/jemds/2014/2121
|View full text |Cite
|
Sign up to set email alerts
|

To Compare the Effectiveness of Myofascial Release Technique Versus Positional Release Technique With Laser in Patients With Unilateral Trapezitis

Abstract: BACKGROUND AND OBJECTIVE:Trapezius pain is the classic stress pain and it is the most common musculoskeletal disorder. It is usually caused by placing too much stress or strain over the trapezius muscle. The upper trapezius muscle is designated as postural muscle and it is highly susceptible to overuse. Trapezius muscles help with the function of neck rotation, side bending and extension. Tightness in the muscles can decrease the range of motion of the neck. The decrease in motion can negatively affect the mob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…The study aligns with findings by Soumik Basu et al, which demonstrated that PRT reduced tissue tension, normalized local vascularization, and decreased pain from ischemia (16). A key strength of this research is its randomized design and the use of a standard Numeric Pain Rating Scale and universal goniometer, which enhances the reliability and comparability of the results.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The study aligns with findings by Soumik Basu et al, which demonstrated that PRT reduced tissue tension, normalized local vascularization, and decreased pain from ischemia (16). A key strength of this research is its randomized design and the use of a standard Numeric Pain Rating Scale and universal goniometer, which enhances the reliability and comparability of the results.…”
Section: Discussionsupporting
confidence: 86%
“…Despite the effectiveness of both ART and PRT in treating myofascial pain associated with trigger points, comparative research between the two is scarce. Therefore, this study aims to evaluate the relative effectiveness of the active release approach (involving patient participation) and positional release therapy (administered passively) (15,16). Determining whether ART or PRT is more beneficial could significantly enhance clinical practices and patient rehabilitation for calf pain caused by trigger points.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Ravish et al [18] compared the effectiveness of myofascial release technique vs. positional release technique with laser in patients with unilateral trapezitis. A total of 60 subjects with unilateral upper trapezius spasm were randomly allocated into 2 groups: A and B. Laser treatment was common to both groups; myofascial release technique was applied in group A and positional release therapy in group B for alternatively 3 days for 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in motion can negatively affect the mobility of the cervical joints restricted range of motion increases chances of muscle going into tightness. 4 TECAR treatment can operate in two electric charge transfer modes: capacitive and resistive. The reactions induced by the capacitive system via the capacitive electrode are concentrated on tissues with greater electrolyte concentrations.…”
Section: Introductionmentioning
confidence: 99%